Current Planning for Internal Audit of Risk Assessment of the Company Activities - М. SHYGUN (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
Lack of management control of the activity risks creates critical operating conditions for the enterprise, in which the financial indicators may change unexpectedly and unfavorably. Avoidance of the risks of an entity's activity is possible if effective interaction is made primarily between economic security and internal audit departments. Productive work of internal auditors to identify, evaluate and reduce the impact of risks on the performance of the enterprise is possible with its proper organization. The article describes the key principles for planning the activities of internal auditors to ensure the quality of audit procedures. Approaches to the organization and planning of the Internal Audit Department's work on identifying risks of the entity's activities, minimizing them and preventing them in the future are disclosed. A working plan for the application of audit procedures in the department of accounting, cashier and warehouse is presented, which demonstrates procedures for identifying and assessing such types of risks as market, payment, currency, financial, tax, credit, loss of assets. The working plan of the audit procedures developed contains the most effective procedures, depending on the objects of the audit, determines the scope of the audit, the procedure of its carrying out, responsible executors, the terms of the procedures. The use of the following suggestions for the planning of internal audit allows to apply qualitatively different forms and methods of audit, types of audit procedures, specialize the audit activities, correctly establish the order of audits, take into account the results of audit in the preparation and approval of various types of enterprise reports.